Establishment of terrestrial mammals on former reservoir beds following large dam removal on the Elwha River, Washington, USA - McCaffery, Rebecca M.; Cendejas-Zarelli, Sara J.; Goodwin, Katy R.; Happe, Patricia J.; Jenkins, Kurt J.; Sager-Fradkin, Kimberly A. (Frontiers in Ecology and Evolution, 2024)
Terrestrial wildlife species are important yet often overlooked taxa in the recovery of ecosystems following dam removal. Their presence can shape ecosystem recovery, signal restoration of ecosystem function, and influence food web dynamics and nutrient transfer. We used camera traps to examine seasonal use of two former reservoir beds and an upstream reference reach by the mammalian community following the removal of two large dams on the Elwha River, Washington, USA. For certain taxa, we compared current species use to data collected prior to dam removal. Camera traps revealed use by at least fifteen mammal species, including but not limited to American black bear (Ursus americanus), Columbian black-tailed deer (Odocoileus hemionus columbianus), Roosevelt elk (Cervus elaphus roosevelti), puma (Puma concolor), coyotes (Canis latrans), bobcats (Lynx rufus), and snowshoe hares (Lepus americanus). Coyotes were found mostly lower in the watershed outside the Olympic National Park boundary, while other species were distributed throughout the restoration area. We did not see major differences in species composition between the restoration areas and the upstream reference reach, though number of detections across study reaches differed for most species. Unlike previous findings, black bears were observed across all seasons in this study, suggesting a shift in seasonal use since dam removal. Full restoration of the terrestrial wildlife community will take decades to unfold, but early patterns demonstrate rapid establishment and use by wildlife on new riparian surfaces that will continue to evolve with restoration of fish and vegetation communities. 1 Introduction